The Impact of Sequential Spelling Instruction on Writing Fluency in Elementary ESL Students - Masandra Citra Ardila; Tiyas Saputri; Edi Pujo Basuki; Mujad Didien Afandi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Writing fluency is an essential component of literacy development among elementary English as a Second Language (ESL) learners. However, many young learners experience difficulties in English spelling due to its irregular orthographic system, which often hinders writing accuracy and fluency. This study aimed to examine the impact of Sequential Spelling Instruction (SSI) on students' word-writing fluency and accuracy. A quantitative study employing a quasi-experimental one-group pretest-posttest design was conducted with 19 second-grade students at Wachid Hasyim Islamic Elementary School. Participants received a 12-week SSI intervention designed to improve spelling through explicit, sequential, and pattern-based instruction. Data were collected using writing pre-tests and post-tests, classroom observations, and students' writing documentation. Writing performance was assessed using Raw Writing Score, Words per Minute (WPM), and Correct Word Sequences (CWS). Descriptive statistics, paired t-tests, and ANCOVA were used to analyze the data. The findings demonstrated improvements across all writing measures following the intervention. The mean Raw Writing Score increased from 5.00 to 8.11, WPM improved from 1.67 to 2.70, and CWS increased from 2.00 to 3.00. The paired t-test indicated a statistically significant improvement in writing performance (t(19) = −10.10, p < .001), while ANCOVA confirmed that the positive effect remained significant after controlling for pre-test scores. These findings suggest that Sequential Spelling Instruction effectively enhances writing fluency and spelling accuracy among young ESL learners by reducing cognitive load during the writing process. The study highlights SSI as a promising instructional approach for improving early literacy development in elementary English classrooms.